Pengaruh Arus Kas Operasi, Tingkat Hutang dan Konsentrasi Pasar Terhadap Persistensi Laba - Dika Triyani Putri; Muhammad Aufa (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to examine and analyze the effect of accounting conservatism, capital structure, firm size on earnings persistence. This type of research is quantitative research. The sampling method in this study was a purposive sampling method, namely the selection of samples based on predetermined criteria. The sample for this study uses manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for 2019-2021 with 98 research data. The analytical method used is multiple linear regression analysis using the IBM SPSS statistics 22 program. The results show that the leverage and market concentration has a significant effect on earnings persistence. Meanwhile, the variable operating cash flow have no effect on earnings persistence.